Left Atrial Remodeling and Function in Advanced Heart Failure With Preserved or Reduced Ejection Fraction. (March 2015) - Melenovsky, Vojtech; Hwang, Seok-Jae; Redfield, Margaret M.; Zakeri, Rosita; Lin, Grace; Borlaug, Barry A.
<x xml:space="preserve">Abstract</x> Background— Left atrial (LA) structure and function are altered in most heart failure (HF) patients, but there may be fundamental differences in LA properties between HF with preserved (HFpEF) and reduced ejection fraction (HFrEF). Methods and Results— One hundred ninety-eight HF patients (51% HFpEF, New York Heart Association 3.1±0.7) and 40 HF-free controls underwent catheterization, echocardiography, and follow-up. Compared with controls, HF patients had larger and more dysfunctional left atria. At identical mean LA pressure (20 versus 20 mm Hg; P=0.9), HFrEF patients had larger LA volumes (LA volume index 50 versus 41 mL/m2; P<0.001), whereas HFpEF patients had higher LA peak pressures, lower LA minimal pressures, higher LA stiffness (0.79 versus 0.48 mm Hg/mL; P<0.001), greater LA pulsatility (19 versus 13 mm Hg; P<0.001), and higher wall stress variations. Despite smaller LA volumes, better function, and less mitral regurgitation, HFpEF patients had more atrial fibrillation (42 versus 26%; P=0.02). LA dysfunction was associated with increased pulmonary vascular resistance and right ventricular dysfunction in both HF phenotypes. After a median follow-up of 350 days, 31 HFpEF and 28 HFrEF patients died. LA function (total LA EF) was associated with lower mortality in HFpEF (hazard ratio 0.43; 95% confidence interval, 0.2–0.9; P<0.05), but not in HFrEF. Conclusions— HFrEF is characterized by greater eccentric LA remodeling, whereas HFpEF by increased LA stiffness, which might contribute to greater atrial fibrillation burden. LA function is associated with pulmonary vascular disease and right HF in both HF phenotypes, but is associated with outcome more closely in HFpEF, supporting efforts to improve LA function in this cohort.